Question
Solve \( 3-2 x=7-6 x \) \( x=\ldots \)
Ask by Watkins Phillips. in Spain
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( x=1 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
The Deep Dive
To solve the equation \( 3 - 2x = 7 - 6x \), start by isolating \( x \). First, add \( 6x \) to both sides to combine like terms: \[ 3 - 2x + 6x = 7 \] This simplifies to: \[ 3 + 4x = 7 \] Next, subtract 3 from both sides: \[ 4x = 4 \] Finally, divide by 4 to solve for \( x \): \[ x = 1 \] So, the solution is \( x = 1 \).